Small-Scale Farmers' Preference in Adopting Geographical Indications’ Code of Practice to Produce Coffee in Indonesia: A Choice Experiment Study - Laksono Pandu (EDP Sciences, 2021)
Geographical Indication is a type of collective intellectual property that producers may use to capture the place-related value expressed in their product which involve the physical and anthropic characteristics of the production area. There is GI’s Code of Practice (CoP) that should be adopted by farmers as reference standard to maintain GIs product consistency and definition requirements. Understanding farmer preferences and incorporating them into the development of improvement of GIs’ certification schemes is thought to result in more internalized, and thus more efficient standards. This study aims to 1) investigate the small-scale farmers’ preferences and the influence of socio-economics characteristics rejecting GIs’ scheme; and 2) develop strategies to increase farmers participation on GIs’ scheme. Choice Experiment method and Conditional Logit Model (CLM) were used to estimate preferences of 157 small-scale coffee farmers for accepting GIs’ scheme. The findings suggest that premium price, coffee processing, technical assistance, and selling agreement are all GIs’ attributes that could increase small-scale farmers’ utility. More incentives are required to compensate farmers due to the loss of utility caused by pesticide bans and farm inspection. Based on CLM, the study found that farmers have clear preferences for and against certain aspects of GIs’ CoP scheme.